RHEUMATOID ARTHRITIS AND PREGNANCY - N. M. Kosheleva (Научно-практическая ревматология, 2014)
Rheumatoid arthritis (RA) generally starts at the age when many women have already become mothers; however, it may occur in childhood or adolescence. Furthermore, there has been recently a women’s tendency to plan pregnacy for a more mature age, which necessitates a discussion about gestation in this disease. Investigation of mechanisms pregnancy can influence the development of RA both in the gestation and long-term periods is of important theoretical and practical value. The results of these investigations may be used to develop new treatments for RA and management tactics for patients during pregnancy and lactation. The  aper gives the data available in the literature on fertility in RA, impact of pregnancy on its activity and that of RA on the course and outcomes of gestation, as well as current ideas on lactation and use of oral contraceptives in RA. Particular attention is given to drug therapy in pregnant and breastfeeding women with RA: groups of anti-rheumatic drugs are considered in detail in relation to the safety of or a potential risk from their use. A therapeutic algorithm and recommendations for pregnancy planning and a follow-up of patients with RA during gestation are proposed.